UNDERSTANDING DISSENT OF POLICE OFFICERS ON INTERNET FORUMS: CASE OF MEMURLAR.NET - Yuksel, Yusuf; Tosun, Hamza (European Scientific Journal, ESJ, 2013)
This article analyzed the primary themes of organizational dissent of police officers displayed on the forum pages of the web sites and individual, relational, and organizational determinants of dissent. In addition, it discussed the role of anonymity and its effect in dissent strategies displayed in online forums. The findings suggest that organizational problems, legal regulations and manager’s approaches were the main themes of police officers’ dissent in this particular online forum. In terms of determinants of dissent, holding non-managerial position, low quality relationships between superiors and subordinates, and strict hierarchical structure were found to be the main determinants of organizational dissent on the online forums. The anonymous nature of postings certainly provided an opportunity to express dissent with reduced fear of retribution or termination. However, anonymity also raised the question of validity of postings, the identity of participants and decreases the impact of postings.